2020
DOI: 10.1021/acsmedchemlett.9b00530
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pyrazolo[3,4-d]pyrimidine Kinase Inhibitors as Potential Clinical Candidates for Glioblastoma Multiforme

Abstract: Glioblastoma multiforme (GBM) is the most aggressive primary brain tumor. Residual cells at the tumor margin are responsible for up to 85% of GBM recurrences after standard treatment. Despite this evidence, the identification of compounds active on this cell population is still an underexplored field. Herein, starting from the knowledge that kinases are implicated in GBM, we evaluated three in-house pyrazolo [3,4-d]pyrimidines active as Src, Fyn, and SGK1 kinase inhibitors against patient derived cell lines fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…The core cells show a clear correlation with published GBM expression data whereas the invasive margin population shows no correlation with any of the TCGA cell lines. This is in agreement with recent evidence that reveals an extensive degree of intra-tumour heterogeneity in GBM resulting from a clonal evolution process producing a completely different genetic pattern in the core compared with the invasive margin [46]. This different molecular signature is critical for the selection potential pharmacotherapies for clinical application.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The core cells show a clear correlation with published GBM expression data whereas the invasive margin population shows no correlation with any of the TCGA cell lines. This is in agreement with recent evidence that reveals an extensive degree of intra-tumour heterogeneity in GBM resulting from a clonal evolution process producing a completely different genetic pattern in the core compared with the invasive margin [46]. This different molecular signature is critical for the selection potential pharmacotherapies for clinical application.…”
Section: Discussionsupporting
confidence: 91%
“…Despite multiple clinical trials and research efforts, GBM continues being the most aggressive of all forms of cancer with very limited clinical options to stop progression and dissemination of the tumor. GBM constitutes a complex of interacting cell types with a core population responding to treatments and an invasive margin population that has proved refractory to intervention [46]. Unfortunately, all efforts to cure this type of cancer have failed to significantly extend median survival times [4].…”
Section: Discussionmentioning
confidence: 99%
“…The compound demonstrated low micromolar IC 50 values (7–11 μM) against the three cell lines studied. 122 A prodrug strategy was used to improve the solubility of 9 compounds from the pyrazolopyrimidine library, including 70 , through addition of a water-solubilising group containing a N -methyl piperazine. The prodrug of 70 was the most efficient and demonstrated a comparable efficacy to 70 in vivo in an orthotopic model of glioblastoma multiforme (GBM).…”
Section: Pyrazolo[34- D ]Pyrimidines In Preclinicmentioning
confidence: 99%
“…We previously reported that Si306 in combination with radiotherapy significantly inhibited the growth of human GBM U87 cell line xenografts in nude mice compared to the control and single treatment [40]. Our recent study showed that Si306 induced apoptotic death in patient-derived cell lines from the invasive region and core of GBM [41]. Both Src tyrosine kinase inhibitors (STKIs), Si306 and its prodrug, were shown to successfully pass the blood-brain barrier (BBB) [40].…”
Section: Introductionmentioning
confidence: 99%